The magnolia story (with bonus content) ebook - Gaines, Chip (2016)
This eBook includes the full text of the book plus an exclusive additional chapter from Chip and Joanna that is not found in the hardcover. An exclusive look at America's first family of renovation! Taking you behind the scenes, Chip and Joanna Gaines share the story of how they met, the ups and downs of being an entrepreneurial couple, and how they built a life they love. The Magnolia Story is the first book from dynamic husband-and-wife team Chip and Joanna Gaines, stars of HGTV's Fixer Upper. Offering their fans a detailed look at their life together, they share everything from the very first renovation project they ever tackled together to the project that nearly cost them everything; from the childhood memories that shaped them, to the twists and turns that led them to the life they share on the farm today. While they both attended Baylor University in Waco, their paths didn't cross until Chip checked his car into the local Firestone tire shop where Joanna worked behind the counter. Even back then Chip was a serial entrepreneur who, among other things, ran a lawn care company, sold fireworks, and flipped houses. Soon they were married and living in their first fixer upper. Four children and countless renovations later, Joanna garnered the attention of a television producer who noticed her work on a blog one day, leading to the incredible Fixer Upper phenomenon. In The Magnolia Story, fans will finally get to join the Gaines family behind the scenes and discover: The time Chip ran to the grocery store and forgot to take their new, sleeping baby Joanna's agonizing decision to close her dream business to focus on raising their children When Chip buys a houseboat, sight-unseen, and it turns out to be a leaky wreck Harrowing stories of the financial ups and downs as an entrepreneurial couple Memories and photos from Chip and Jo's wedding The significance of the word magnolia and why it permeates everything they do The way the couple pays the popularity of Fixer Upper forward, sharing the success with others, and bolstering the city of Waco along the way And yet there is still one lingering question for fans of the show: Is Chip really that funny? "Oh yeah," says Joanna. "He was, and still is, my first fixer upper."